A Thorny Path $1 (BVolume 04s - Ebers, Georg, 1837-1898; Bell, Clara, 1834-1927 (Salt Lake City, UT : Project Gutenberg, 2004)
"A Thorny Path $1 (BVolume 04" by Georg Ebers is a historical novel likely written in the late 19th century. This installment explores themes of love, loyalty, and the complexities of personal and political conflict during a tumultuous period of Roman history. The narrative revolves around Melissa, a young artist's daughter, and her relationships with her lover Diodoros, her brother Alexander, and Agatha, a Christian girl, as they navigate dangers associated with imperial pursuits and personal aspirations. The opening of the book introduces us to a critical moment where Melissa and her friend Agatha share a deep bond forged through their shared losses and experiences. The atmosphere is filled with tension, as Melissa rushes to aid her ailing lover Diodoros. The chapter weaves through their interactions and the broader societal changes surrounding them, including their encounters with influential figures like Andreas and Ptolemaeus. As the narrative unfolds, hints of danger related to political machinations become evident, especially concerning Alexander's reckless behavior that threatens their family. Through poignant dialogue and detailed scenes, we see Melissa's determination emerge amid alarming circumstances, setting the stage for the unfolding drama of love and sacrifice. (This is an automatically generated summary.)s
Release date is 2004-04-01
This eBook was produced by David Widger
Keywords: Egypt -- History -- 30 B.C.-640 A.D. -- Fiction; German fiction -- Translations into English